2003
DOI: 10.2166/wh.2003.0020
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of culture-independent, library-independent genotypic methods of fecal source tracking

Abstract: Culture-independent fecal source tracking methods have many potential advantages over library-dependent, isolate-culture methods, but they have been subjected to limited testing. The purpose of this study was to compare culture-independent, library-independent methods of fecal source tracking. Five laboratories analysed identical sets of aqueous samples that contained one or more of the following sources: sewage, human feces, dog feces, cattle feces and gull feces. Two investigators used methods based on PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…We previously showed that seawater did not affect the PCR detection limit for HF134, HF183, CF128, and CF193 (6,12,17), as well as two other Bacteroidales host-specific markers, PF163 and DF475 (6,12,17), but we did not examine the effect of seawater on survival of the marker cells. However, PCR assays could in theory detect dead cells, in contrast to indicator bacteria assays that depend on live cells.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We previously showed that seawater did not affect the PCR detection limit for HF134, HF183, CF128, and CF193 (6,12,17), as well as two other Bacteroidales host-specific markers, PF163 and DF475 (6,12,17), but we did not examine the effect of seawater on survival of the marker cells. However, PCR assays could in theory detect dead cells, in contrast to indicator bacteria assays that depend on live cells.…”
Section: Discussionmentioning
confidence: 84%
“…1). Previous studies demonstrated that 100-ml water samples gave detection levels similar to those for indicator bacterium assays (5, 6,13,17). Therefore, for each sample, 100 ml of water was filtered through 0.2-l-pore-size Supor-200 filters (Whatman).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite early attempts to utilize the higher ratio of fecal coliforms (E. coli) to enterococci to discriminate human from animal (bird) fecal sources (Geldreich and Kenner 1969;Geldreich 1976), due to varying differential die-off (and even growth) of either E. coli or enterococci in different aquatic environments (Davies et al 1995;Genthner et al 2005), interpretation of such ratios is generally confounded. Hence, alternative approaches have been explored, and despite continued efforts, no robust E. coli nor enterococci markers have been reported (Field et al 2003;Jiang et al 2007;Whitman et al 2007;Mohapatra et al 2008;Lanthier et al 2010). There are promising bird markers, however, which come from Catellicoccus 16S rRNA gene markers (Lu et al 2011;Green et al 2012;Ryu et al 2012a, b), and one demonstrated to identify Sandhill Crane excreta (Ryu et al 2012a, b) was used and supported in the current study (Table 1).…”
Section: Key Markers Of Crane Pollutionmentioning
confidence: 99%
“…These methods include detection of human enteroviruses or adenoviruses (16,22), host-specific species of Bacteroides (1), or virulence genes in E. coli (6). Several of these approaches were shown to be useful in detecting human sources of fecal contamination but did not necessarily identify all of the contributing hosts when multiple sources were present (11).…”
mentioning
confidence: 99%